Awaken the Giant Within : How to Take Immediate Control of Your Mental, Emotional, Physical and Financial Destiny - Robbins, Anthony (New York A Fireside Book, 1991)
Author shows how to take immediate control of mental, emotional, physical, and financial destiny with strategies from his Date with Destiny seminar.
Includes Index and Illustration.
Keywords: Success -- Self-Actualization (Psychology) -- Control (Psychology)